Simulasi Efek Konduktivitas Hidrolik pada Intrusi Air Laut - Ferdy; Tirza Wungkana; Dolfie Paulus Pandara; Maria D. Bobanto; Hanny F. Sangian; Adey Tanauma; Seni H. Tongkukut; Hesky S. Kolibu (Jurnal Penelitian Pendidikan IPA, 2025)
This research has been conducted with the aim of simulating the process of seawater intrusion using SEAWAT software and assessing the factors causing seawater intrusion. In this simulation, variations in hydraulic conductivity and aquifer material types are explored to understand their impact on the distribution of water levels. The simulation results are presented in the form of simulated concentration plots used to visualize concentration distribution with color gradients reflecting changes in concentration values. Additionally, the direction of groundwater flow is represented by arrows, aiding in understanding the movement patterns of dissolved substances within the aquifer. Simulated head plots are created using colors and contour lines. The resulting simulated head plots depict changes in color and contour lines that represent variations in water levels throughout the aquifer. Color gradients from yellow to purple indicate a decrease in water levels, while contour lines indicate the direction of groundwater flow. Furthermore, changes in the shape of contour lines from straight to curved depict changes in the topography or hydrogeological characteristics within the aquifer. The simulations are carried out by considering changes in hydraulic conductivity and aquifer material characteristics. In the context of this research, hydraulic conductivity is considered a key factor influencing the movement of dissolved substances within the aquifer, and through this analysis, it is found that hydraulic conductivity significantly affects water level distribution and groundwater flow patterns.